Prevalence and Outcomes of Orthostatic Hypotension in Hemorrhagic Stroke Patients During Hospitalization - Pui Kit Tam; Guhan Ramamurthy; Lavanya Rawat; Serene Huang; Jeong Hoon Lim (Neurology International)
Background/Objectives: Orthostatic hypotension (OH) is highly prevalent in hospitalized patients and can lead to major consequences. The prevalence of OH among patients with stroke has also been reported to be high in in-patient cohorts. However, no previous analysis has focused exclusively on patients with hemorrhagic stroke, a group that may have a different disease profile, including a greater need for blood pressure control and surgical intervention. This study aims to examine the prevalence of OH, its risk factors, and potential impact in patients who were hospitalized due to hemorrhagic stroke. Methods: A retrospective analysis of in-patient records between 1 January 2021 and 30 April 2023 was conducted for patients with stroke due to intracerebral hemorrhage (ICH) or subarachnoid hemorrhage (SAH) who were referred to rehabilitation at a tertiary hospital in Singapore. OH was defined as a drop in systolic blood pressure of ≥20 mmHg or diastolic blood pressure of ≥10 mmHg during the sit-up test as part of the rehabilitation assessment. Additional data collected included demographic information, length of stay, antihypertensive medications used at the time of assessment, comorbidities, and discharge functional outcomes as measured by a modified Rankin Scale. Results: A total of 77 patients (65 [84.4%] with ICH and 12 [15.6%] with SAH) were included in the analysis. The prevalence of OH was 37.7%. A history of surgical intervention was identified as the major risk factor for the development of OH (odds ratio 4.28, 95% confidence interval 1.37 to 13.35, p = 0.009). There was no difference in hospital length of stay or discharge modified Rankin Scale scores between the two groups. Conclusions: OH was frequently observed among patients with hemorrhagic stroke during the acute/subacute stage and should be monitored, especially in patients who require surgical intervention.